Barriers and incentives for choosing to specialise in mammography– A survey of Australian undergraduate diagnostic radiography students. Issue 4 (November 2018) - Warren-Forward, H.M.
Abstract: Introduction: There is a projected shortage of radiographers working in breast screening in Australia. This study aimed to examine the perceived barriers and potential incentives among current undergraduate diagnostic radiography students to train, specialise and work in mammography. Methods: A survey was undertaken to assess students' experience of six modalities during both University study and clinical practice. Students were asked to rank their priority of which they would want to specialise and if training and working in mammography was an option. Results: From 248 students invited to participate, 101 students replied to the survey. Students indicated that they had been taught all modalities, however not all students had experienced them on clinical placement. Most students had observed or performed ultrasound (US) (90%, 90%), Computed Tomography (CT) (97%, 75%) and fluoroscopy (80%, 52%), though very few had experience of mammography (55%, 8%). US, CT, and MRI were the modalities that most students would like to specialise in. Male students reported being discriminated against working in mammography as this is "female only" work. Conclusion: Students have more clinical access to the major modalities of US, CT and MRI, and this appears to be a major factor into why student wish to specialise in these modalities. Role extension and higher wages were given as possible incentives that would make specialising in Mammography more appealing. The gender divide may have to be bridged to enable crucial recruitment as male students feel discriminated against. Highlights: Experiencing a modality in their degree increased motivation to work in that modality. The majority of students placed ultrasound as their preferred area of specialisation. Only 8% placing mammography as their preferred speciality modality after graduation. More females (35%) than males (14%) wished to specialise in mammography. Male students identified gender inequalities in regards to the mammography workforce.